Suphisellus grossoi sp. n., a new burrowing water beetle from South America, and notes on S. flavolineatus (Régimbart, 1889) and S. grammicus (Sharp, 1882) (Coleoptera: Noteridae) - Urcola, Juan I.; Benetti, Cesar J.; Baca, Stephen M.; Michat, Mariano C. (Zootaxa, 2020)
Suphisellus grossoi sp. n. is described from the Reserva Natural del Bosque de Mbaracayú, Canindeyú department, Paraguay. Diagnostic characters are described and illustrated in detail. New records are provided for S. flavolineatus (Régimbart, 1889) and S. grammicus (Sharp, 1882), which are also briefly diagnosed. Suphisellus melzeri Zimmermann, 1925 is proposed as a junior subjective synonym of S. flavolineatus (syn. n.), and lectotypes are designated for both taxa.